Optimal Policy and Network Effects for the Deployment of Zero Emission Vehicles - Guy Meunier; Jean-Pierre Ponssard (Center for Economic Studies and ifo Institute (CESifo), 2018)
We analyze the impact of indirect network effects in the deployment of zero emission vehicles in a static partial equilibrium model. In most theoretical analysis direct and indirect effects are conflated, and relatively few authors have explicitly considered indirect network effects. We also introduce the market power of vehicle producers and scale effects in the production function. The model exhibits a multiplicity of local social extrema and of market equilibria, suggesting a possibility of lock-in. The optimal set of subsidies is derived so that the Pareto dominating market equilibrium would coincide with the social optimum. This framework is applied to the case of the fuel cell electric (hydrogen) vehicles.
Keywords: C61; 330; E-mobility; network effects; joint incentives for infrastructure and car rebates